PROBLEMATIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI 064025 KECAMATAN MEDAN TUNTUNGAN - Saprin Efendi, Saiful Akhyar Lubis, Wahyudin Nur Nasution (Pascasarjana UIN Sumatera Utara, 2018)
Abstract: The purpose of this research is to find out the teacher’s plan at Islamic education learn teachingat SD of State 064025 Medan Tuntungan, the teacher’s doing at Islamic education learn teaching, theproblem is being faced by teachers under teaching. The obstacles and supports are faced by teacherduring teaching and the solve of teacher’s target at the problem of Islamic education learning This researchused the qualitative method. The research’s result of the problem of Islamic education learning atSD of State 064025 Medan Tuntungan are from the problems, the teacher made designing of learning andmade the exploration diagram of skill via example non example concept, class discussion, concept mapand scientific learning based on thematic. The doing are all the students made panel to write the questionon hand out, demanded them to develop practice via example non example concept, class discussion,concept map and scientific learning based on thematic. The problems are on invitation or apperception atplan, exploration and explanation. The obstacles are less of the parents’ participation, less of attention andevaluation. From the supports are relevant to KTSP and K-13. Audio visual provided the pictures based onconcept map and scientific learning. And the solves are designed evaluation at recitation changing, discussionbased on opinions’ exchanging.Tujuan penelitian ini adalah untuk mengetahui perencanaan guru dalam pembelajaran pendidikan agamaIslam di SD Negeri 064025 Kecamatan Medan Tuntungan, pelaksanaan guru dalam pembelajaran pendidikanagama Islam di SD Negeri 064025 Kecamatan Medan Tuntungan, problematika yang dihadapi guru PAI,faktor penghambat dan pendukung yang dihadapi guru PAI dan solusi yang dicapai guru PAI dalamproblematika pembelajaran pendidikan agama Islam. Penelitian ini menggunakan metode kualitatif. Hasilpenelitian pertama bahwa problematika pembelajaran PAI di SD Negeri 064025 Kecamatan MedanTuntungan ini dari perencanaannya membuat desain pembelajaran dan membuat diagram pengembangankecakapan melalui konsepexample non example, diskusi kelas, peta konsep dan pembelajaran saintifikberbasis tematik. Pelaksanaannya setiap kelompok menuliskan pertanyaan dalamhand out. Problematikanyadalam invitasi atau apersepsi, dalam perencanaan, dalam eksplorasi serta dalam penjelasan. Faktor penghambatnyakurangnya daya dukung dari para orang tua, kurangnya atensi besar, kurangnya evaluasi. Dari segipendukung relevan Kurikulum KTSP dan K-13. Sedangkan solusinya membuat evaluasi dalam pertukaranresitasi, diskusi dan Diskusi berdasarkan saling berbagi pendapat dan gurunya membuat tes psikomotor.Kata kunci: Problem, Pendidikan dan Pembelajaran